IT supported project based learning framework - Mohammed Hamouda, Mohammed Elgasim (2010)
Project-based learning involve a group of students completing a project with the aim of engaging students in deep learning and thus meeting specific learning outcomes. Performance might be assessed on individual or group basis by taking into account the depth of understanding of the content, the quality of artifact produced and the contributions made by each individual group member. Assessment of individual work might be unfair due to the fact that instructors are unable to monitor closely students? participations and contributions. In order to solve this, peer assessment has been used by some instructors. However, there is a tendency that students are biased towards their group members. Using IT as a medium in completing group projects can be a solution to these constraints. Through IT support, instructors not only will be able to view the evidences of individual student learning but also the process of learning and completing the project. Selecting the appropriate IT tools for collaboration and design of the project question are essential factors towards effective project based learning is. The main objective of this paper is to present a field experiment of IT Supported Project Based Learning through the use of collaboration software by second year students enrolling the Database Programming course. Pre and post questionnaire has been used as the data collection tool. Findings show that students found that they managed to complete the project according to schedule and work better as a team compared to completing group projects without IT support. From the point of view of the instructor, the process of students contributions is visible thus enable the activity of providing students feedback in terms of learning and motivating them in completing their projects.